2021
DOI: 10.3389/fphys.2021.697059
|View full text |Cite
|
Sign up to set email alerts
|

Amadis: A Comprehensive Database for Association Between Microbiota and Disease

Abstract: The human gastrointestinal tract represents a symbiotic bioreactor that can mediate the interaction of the human host. The deployment and integration of multi-omics technologies have depicted a more complete image of the functions performed by microbial organisms. In addition, a large amount of data has been generated in a short time. However, researchers struggling to keep track of these mountains of information need a way to conveniently gain a comprehensive understanding of the relationship between microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Amadis is a database that provides experimentally supported microbiota-disease associations [24]. With aid of Amadis's network analysis tools, we found that there could be an association between CXCL8, Fusobacterium nucleatum, and human diseases (including inflammatory bowel disease and colon cancer).…”
Section: Amadismentioning
confidence: 97%
“…Amadis is a database that provides experimentally supported microbiota-disease associations [24]. With aid of Amadis's network analysis tools, we found that there could be an association between CXCL8, Fusobacterium nucleatum, and human diseases (including inflammatory bowel disease and colon cancer).…”
Section: Amadismentioning
confidence: 97%
“…On the other hand, microbes, including Lactobacillus reuteri ( 9 ), Lactobacillus gallinarum ( 10 ), and Streptococcus thermophilus ( 11 ) are reported to suppress tumorigenesis and cancer progression via multiple pathways, such as inhibiting the metabolism of tumor proliferation ( 11 ). To date, several databases have been constructed to document these positive or negative associations between gut microbiota and tumor development, such as mBodyMap ( 12 ), gutMDisorder ( 13 ), GMrepo ( 14 ), and Amadis ( 15 ). However, the important effects of microbiota on the efficacy and toxicity of anticancer drugs have not been systematically documented to date.…”
Section: Introductionmentioning
confidence: 99%
“…Amadis (http://gift2disease.net/GIFTED) is a database that provides experimental support for microbialdisease associations [23]. In this study, we used Amadis to explore the possible associations between FUTs, intestinal ora, and colon cancer.…”
Section: Amadis Databasementioning
confidence: 99%